ANALYSIS OF PHYTOCHEMICALS FROM EUPATORIUM ODORATUM FLOWER - Deepa G, Muricken; Jofeena, Joy (International Journal of Ayurveda and Pharma Research, 2015)
The Eupatorium odoratum is included in sun flower family Asteraceae has many properties as anti-bacterial, anti-mycobacterial properties. It also contains many phytochemicals. It used as tea in many places. An ointment prepared from the leaves of Eupatorium odoratum is has been shown to promote the healing of soft tissue wounds by enhancing the proliferation and migration of fibroblast. It has been identified that the presence of antioxidants and other bioactive compounds might have helped the people to use the leaves and roots of this plant as natural medicine. It used as medicinal as well as ornamental plant. Successive extracts from dried flowers of Eupatorium odoratum were investigated for the presence of phytochemicals. Methanol extract was used for the phytochemical and antibacterial studies. Aqueous extracts of Eupatoriumodoratum was used for the insecticidal and larvicidal activity. As a result it was found that the plant flowers have insecticidal and larvicidal activity and a slight range of antibacterial activity. Aqueous extract exhibited the presence of enzyme polyphenol oxidase. The extract was subjected to ammonium sulfate precipitation and dialysis to precipitate proteins. It was then eluted out using ion exchange chromatography and partially purified. The PPO have a wide range of applications, it is an important natural component in dye industry, it is good for bioremediation as it cleaves phenol rings of many of the petroleum compounds which cause soil pollution.